FACTORS AFFECTING THE ECONOMIC POLICY OF FOOD IN INDONESIA - Asriani Asriani; Dhian Hedhiansyah (Mega Aktiva, 2019)
Food security is one indicator of economic growth of a country and may reflect the prosperity as well as a benchmark of the the welfare level, particularly in terms of people’s production and consumption. Food security policies need to be supported through increased production of commodities. Corn is one crop with a strategic role due to its position as the main source of carbohydrates and protein. To increase the production of corn, there should be the policy inputs or factors of production done by increasing the planting area and the productivity of corn crops in Indonesia. This study aims to analyze the factors of production that can increase the production of corn farming. The data used are time series data with Nerlove model as the data analysis way. The results indicate that the harvest area factor and productivity factor may influence the increasing of farm production of corn; it thus can serve as the basis of economic policy-making related to the food sector in Indonesia.